Being a Young Sami in Sweden: Living Conditions, Identity and Life Satisfaction - Omma, Lotta M.; Holmgren, Lars E.; Jacobsson, Lars H. (Umeå University Library, 2011)
Objective: The aim of the present study was to illuminate the contemporary cultural reality of being a young Sami in Sweden, with special reference to issues such as identity/self-perception, autonomy, and experiences of being ill treated and discrimination. Design: The study comprises a qualitative and a quantitative part. The qualitative part includes meetings, discussions and dialogues with young Sami and others. The quantitative part includes a questionnaire on socioeconomic conditions, Sami ethnicity, experiences of being ill-treated because of a Sami background, specific questions on identity and self-perception, questions about self-determination, and thoughts and expectations of the future. The sample consists of 876 young Sami aged 18–28, of whom 516 (59 per cent) responded to the questionnaire. Results: A majority are proud to be Sami and wish to preserve their culture. 71 per cent have a close connection to a Sami community. Most of the young Sami have had to explain and defend their culture and way of life. Nearly half had perceived discrimination or ill-treatment because of their ethnicity, with reindeer herders reporting a higher degree of ill-treatment (70 per cent). Reindeer herders exist in a severe environment with an insecure legacy. Most of the young Sami in this study have a positive self-perception and think that their lives are meaningful. Very few dropped out of school and very few are unemployed. Conclusion: We believe that there are protective factors that potentially explain the well-being of this group; a strong feeling of belonging among the Sami, strong connections to family, relatives and friends and good sociocultural adaptation (to have a job, completed school).